Prioritization vs Zero-Rating: Discrimination on the Internet - Axel Gautier; Robert Somogyi (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper analyzes two business practices on the mobile internet market, paid prioritization and zero-rating. Both violate the principle of net neutrality by allowing the internet service provider to discriminate different content types. In recent years these practices have attracted considerable media attention and regulatory interest. The EU, and until recently the US have banned paid prioritization but tolerated zero-rating under conditions. With prioritization, the ISP delivers content at different speeds and it is equivalent to a discrimination in terms of quality. With zero-rating, the ISP charges different prices for content and it is equivalent to a discrimination in terms of prices. We first show that neither of these practices lead to the exclusion of a content provider, a serious concern of net neutrality advocates. The ISP chooses prioritization when traffic is highly valuable for content providers and congestion is severe, and zero-rating in all other cases. Furthermore, investment in network capacity is suboptimal in the case of prioritization and socially optimal under zero-rating.
Keywords: D21; L12; L51; L96; 330; net neutrality; paid prioritization; zero-rating; sponsored data; data cap; congestion